Design and Implementation of Photovoltaic Single Stage Inverter Connected to Grid - Bayu Prasetyo; Mochamad Ashari; Dedet Candra Riawan (Institut Teknologi Sepuluh Nopember, 2014)
Photovoltaic system that connected to grid is a system which applied for an area that can be reach by transmission line. This system as a support for conventional generating system. If there is a power from PV system, then power demand supplied from photovoltaic generating system. Otherwise, power demand supplied from conventional generating system. As a support conventional generating system, there is many methods to convert photo energy into AC system that connected to grid. One of conventional methods as a two stage inverter, this methods need two process to convert photovoltaic into AC system. First stage, conversion photovoltaic power to DC system. In this stage PV processed by buck boost converter. Second stage, that DC power from first stage changed into AC power system. This two stage process has low efficiency, so we try to make the process simply and more efficiency. New method called single stage inverter can be applied. With this methods, conversion DC power system from PV can be done by single stage process. From this single process, we expext that more efficiency can be achieved.